Empathy in action: cultivating altruism through immersive game experiences - Lorenzo, Samantha B.; Okahata, Leila (Frontiers in Virtual Reality, 2026)
IntroductionImmersive digital games are increasingly explored as tools for fostering empathy and prosocial behavior, yet limited research examines how these effects unfold in virtual reality (VR). This mixed-methods research examined Empathy in Action, a narrative-driven VR game developed for this study that engages players in assisting a distressed child through both physical tasks and moral decision-making.MethodsSixty-four adult participants completed pre- and post-surveys measuring empathy, altruism, immersion, and gameplay effects, followed by semi-structured interviews.ResultsResults revealed a significant increase in altruistic attitudes but a significant decrease in self-reported empathy, suggesting that altruism can be reinforced through immersive decision-making even when emotional resonance tapers post-play. Regression analyses indicated that perceived gameplay effect was the strongest predictor of altruistic outcomes, surpassing demographic or gaming background variables. Qualitative reflections supported these findings, with participants linking in-game helping behaviors to real-life relationships and envisioning applications in education, therapy, and rehabilitation.DiscussionThese results complicate assumptions that empathy and altruism rise in tandem, underscoring the role of reinforcement, moral agency, and reflective engagement in prosocial outcomes. The study advances theory by decoupling empathy and altruism within immersive contexts and highlights the broader potential of VR games as tools for cultivating moral action and social change.